Personal Traits Among a Sample of Teaching and Administrative Stuff in the Secondary Schools of Damascus Governorate (Journal of Hama University, 2021)
This research aimed at identifying the personal traits among a sample of teaching and administrative stuff in the secondary schools of Damascus governorate, and measuring the differences in these traits according to variables of (gender, marital status, job title, and years of experience). The research sample consisted of (251) teachers, principals, counseling psychologists, and administrative employees. The researcher used the scale of Big Five Factors of Personality, which prepared by (Costa & Mcrcae, 1992) after checking its psychometric characteristics.The research results indicated the following:-The order of personal traits among research sample were as following: (conscientiousness, openness to experiences, extraversion, agreeableness and neuroticism). -There were no statistically significant differences between the mean scores of research sample members on the scale of Big Five Factors of Personality according to variable of (gender, marital status, and years of experience). -There were statistically significant differences between the mean scores of research sample members on the (openness to experiences) trait according to variable of (job title) between:- Administrative employees and principals in favor of administrative employees.- Administrative employees and counseling psychologists in favor of administrative employees.